Meningkatkan Hasil Belajar Siswa Dengan Pembelajaran Berbasis Masalah - Suparni Suparni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2017)
Mathematics learning at 5th grade of SDN 21 Batang Anai Kabupaten Padang Pariaman indicated that learning process did not encourage students to apply the concepts in solving problems. It caused the students’ learning achievement become low. This is a classroom action research aimed to improve students’ learning achievement by implementing problem based learning (PBL). Data were obtained through observation and test. Mean of students’ learning achievement from initial observation is 54.63 and become 72.78 in cycle I. Mean of students’ learning achievement is 78.37 in cycle II. Hence, problem based learning can improve students’ learning achievement.